Karakteristik Klinis Otitis Media Akut pada Anak di Puskesmas Wilayah Pedesaan - Julian Mahendra; Zaki alghifari; Zalfa Aditya Putra (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Acute Otitis Media (AOM) is a common middle ear infection in children, particularly in rural areas. This study aims to explore the clinical characteristics of AOM in children treated at rural health centers (puskesmas) and to examine the barriers to effective management. A descriptive qualitative method was employed through a literature review analyzing symptoms, stages, risk factors, and treatment approaches. The findings reveal that AOM in children often begins with an upper respiratory tract infection and presents with sudden ear pain, high fever, sleep disturbances, and ear discharge. Risk factors include young age, poor environmental conditions, and limited access to healthcare services. Management of AOM depends on its clinical stage and requires accurate diagnosis. However, in rural puskesmas, a lack of diagnostic tools and limited public awareness often leads to delayed treatment. Therefore, it is essential to provide health workers with basic ENT training, ensure the availability of diagnostic equipment, and educate parents to enable early detection and prevent complications that could affect a child’s development.